2019
DOI: 10.17569/tojqi.615378
|View full text |Cite
|
Sign up to set email alerts
|

STEM Education for Disadvantaged Students: Teacher and Student Experiences

Abstract: STEM education is based on interrelated and holistic teaching of the disciplines of science, technology, engineering and mathematics. It is important to ensure that STEM education does not address a certain category of society only but that it is also applied to disadvantaged segments of society. The aim of the present study is to identify the opinions of socioeconomically disadvantaged students and their teachers about STEM education experience. The study was planned according to the case study model. The par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…In the preliminary stage of face-to-face education, while teachers prepare a STEM lesson plan, want to reach materials from close quarters, and try to adapt to the physical conditions of the classroom environment, students are encouraged to use the opportunities offered by Web 2.0 technological tools in online education. Similar results are seen in the literature (Bolatli and Korucu, 2018;Bozkurt Altan and Ercan, 2016;Çalış 2020;Sias et al, 2017; In this situation, it is seen that teachers try to make STEM applications based on the learning environment, students, and their own experiences in both forms of application.…”
Section: Conclusion Discussion and Suggestionssupporting
confidence: 87%
“…In the preliminary stage of face-to-face education, while teachers prepare a STEM lesson plan, want to reach materials from close quarters, and try to adapt to the physical conditions of the classroom environment, students are encouraged to use the opportunities offered by Web 2.0 technological tools in online education. Similar results are seen in the literature (Bolatli and Korucu, 2018;Bozkurt Altan and Ercan, 2016;Çalış 2020;Sias et al, 2017; In this situation, it is seen that teachers try to make STEM applications based on the learning environment, students, and their own experiences in both forms of application.…”
Section: Conclusion Discussion and Suggestionssupporting
confidence: 87%
“…Bozkurt Altan & Köroğlu, 2019 drew attention to the incompetency of STEM fields to social injustices and how we can implement STEM in a social justice framework. The study suggested a need for professional development for teachers in STEM education and also the development of action plans for disadvantaged groups by STEM-educated teachers (Bozkurt et al, 2019). Furthermore, the research emphasizes the funding for future STEM education research and STEM-focused activities for disadvantaged groups (Bozkurt et al, 2019) so they can enjoy the benefits of STEM education.…”
Section: Stem Limitationsmentioning
confidence: 98%
“…The study suggested a need for professional development for teachers in STEM education and also the development of action plans for disadvantaged groups by STEM-educated teachers (Bozkurt et al, 2019). Furthermore, the research emphasizes the funding for future STEM education research and STEM-focused activities for disadvantaged groups (Bozkurt et al, 2019) so they can enjoy the benefits of STEM education. Yet numerous studies have indicated a lack of interest and motivation among students towards STEM fields or "STEM pipeline" created a global concern (Sanders, 2009;Kelley & Knowles, 2016) that require the researcher and developers to look deeply into the STEM framework to find and solve the STEM-related problem.…”
Section: Stem Limitationsmentioning
confidence: 98%